FAKTOR-FAKTOR YANG MEMPENGARUHI INDEPENDENSI AUDITOR - Eduarto Unggul Wicaksono, 13.05.52.0095; Kartika, Andi (Students' Journal of Accounting and Banking, 2019)
This study examines the factors that influence the independence of auditors. Factors that influence auditor independence include the provision of other services besides audit services, length of audit relationships with clients, size of public accounting firms, competition between public accounting firms, and audit fees. Populations in this study are all auditors who work in the Public Accounting Firm in Semarang. Sampling was done using the convenience sampling method and the number of samples was 63 respondents. The method of retrieving primary data used was the questionnaire method. Data were analyzed using multiple linear regression models. The results showed that the length of the audit relationship with clients, competition between public accountants, and audit fees had a significant positive effect on auditor independence, while the provision of services other than audit services, the size of public accounting firms had a positive and insignificant effect on auditor independence.